Integrating unity into IoT solutions - Casimiro, M.; Coutinho, C. (Procedia Computer Science, 2025)
This paper investigates the integration of Unity with Internet of Things (IoT) technologies to enhance data visualization and interaction capabilities. Unity, renowned for its capabilities in game development, presents untapped potential within the IoT landscape, particularly in 3D modeling, augmented reality (AR), and virtual reality (VR), which can revolutionize end-user applications. This paper begins with a comprehensive literature review exploring Unity's integration with sensors within the recent years. It proceeds with a detailed technology stack and architecture proposal tailored specifically to a Unity-powered mobile application. The findings underscore the feasibility and effectiveness of Unity's integration into IoT frameworks, promising enhanced user experiences. Future research directions are also explored and look to further explore and optimize this integration, aiming to bridge the gap between cost-effective IoT solutions and groundbreaking data visualization techniques using sensor data.